2022
DOI: 10.3390/jcm11195687
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Pulmonary Diffusing Capacity Decline to HRCT and VQ SPECT/CT Findings at Early Follow-Up after COVID-19: A Prospective Cohort Study (The SECURe Study)

Abstract: A large proportion of patients exhibit persistently reduced pulmonary diffusion capacity after COVID-19. It is unknown whether this is due to a post-COVID restrictive lung disease and/or pulmonary vascular disease. The aim of the current study was to investigate the association between initial COVID-19 severity and haemoglobin-corrected diffusion capacity to carbon monoxide (DLco) reduction at follow-up. Furthermore, to analyse if DLco reduction could be linked to pulmonary fibrosis (PF) and/or thromboembolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…We included 29 consecutive patients from March to May 2020 at Rigshospitalet, Copenhagen University Hospital, Denmark. The patients were a subgroup of the prospective SECURe cohort (Sequelae COVID-19, University Hospital, Rigshospitalet) [ 28 ]. The SECURe cohort included those patients with severe-to-critical COVID-19 in need of hospitalisation and, in some cases, admittance to the intensive care unit (ICU) and mechanical ventilation.…”
Section: Methodsmentioning
confidence: 99%
“…We included 29 consecutive patients from March to May 2020 at Rigshospitalet, Copenhagen University Hospital, Denmark. The patients were a subgroup of the prospective SECURe cohort (Sequelae COVID-19, University Hospital, Rigshospitalet) [ 28 ]. The SECURe cohort included those patients with severe-to-critical COVID-19 in need of hospitalisation and, in some cases, admittance to the intensive care unit (ICU) and mechanical ventilation.…”
Section: Methodsmentioning
confidence: 99%
“…Lung function impairment with low total lung capacity, low forced vital capacity and lung diffusion impairment is common after severe COVID‐19 requiring hospitalization [37, 42]. Similarly, radiological findings have been found in a significant proportion of patients previously hospitalized [43–46]. Three months after confirmed COVID‐19‐related pneumonia, ground glass opacities were found in 75% of patients, reticulations in 30% and residual subpleural infiltration in 13% [47].…”
Section: Manifestationsmentioning
confidence: 99%
“…Besides common pulmonary symptoms, such as breathlessness, chest pain and fatigue, grouped under the term 'long COVID' , numerous studies have reported a severity-dependent reduction in pulmonary diffusing capacity (D L ) (Huntley et al, 2022;Katzenstein et al, 2022;Watanabe et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…After the initial surge of the coronavirus disease 2019 (COVID‐19) pandemic, it became evident that the pulmonary effects of the disease often lasted far beyond the immediate severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection (Crook et al., 2021 ). Besides common pulmonary symptoms, such as breathlessness, chest pain and fatigue, grouped under the term ‘long COVID’, numerous studies have reported a severity‐dependent reduction in pulmonary diffusing capacity ( D L ) (Huntley et al., 2022 ; Katzenstein et al., 2022 ; Watanabe et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation